The movements of yellowfin tuna, blue marlin, and sailfish within the Palau National Marine Sanctuary and the western Pacific Ocean. (1st February 2022) - Filous, Alexander; Friedlander, Alan M; Toribiong, Melvin; Lennox, Robert J; Mereb, Geory; Golbuu, Yimnang
Abstract: We used satellite tags to monitor the movements of yellowfin tuna, blue marlin, and sailfish in the Palau National Marine Sanctuary (PNMS) and provide a first look into their use of this large-scale marine protected area (LSMPA). Tagged fish ranged over a wide geographic area between 1°S to 17°N and 125 to 154°W. Both blue marlin and sailfish exhibited fidelity to the PNMS; however, they dispersed more than 1000 km before returning. The monitoring periods of yellowfin tuna were insufficient to evaluate their long-term movements, but their dispersal from Palau's EEZ occurred in all directions, up to distances of 2010 km. The space use of this pelagic species assemblage overlapped with two bodies of international waters, six EEZs, and the Western and Central Pacific Fisheries Commission's management units seven and three of the western Pacific Ocean. Our results add to the knowledge base on the movements of pelagic species in the PNMS and highlight the need for additional research to determine the long-term movements of these species and the contribution of the PNMS to fisheries management in the western and central Pacific Ocean.